2006
DOI: 10.1096/fj.05-4695fje
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D1 degradation enhances endothelial cell survival upon oxidative stress

Abstract: The understanding of endothelial cell responses to oxidative stress may provide insights into aging mechanisms and into the pathogenesis of numerous cardiovascular diseases. In this study, we examined the regulation and the functional role of cyclin D1, a crucial player in cell proliferation and survival. On H2O2 treatment, endothelial cells showed a rapid down-modulation of cyclin D1. Other D-cyclins were similarly regulated, and this decrease was also observed after exposure to other oxidative stress-inducin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 46 publications
6
31
0
Order By: Relevance
“…In keeping with previous studies from our 7,8,24 and other laboratories, 25,26 H 2 O 2 concentrations used in this paper are within the submillimolar range, and induce negligible EC death in vitro. Therefore the red/ox imbalance achieved is likely close to what is expected to occur in many pathophysiological conditions, for example, reperfusion injury, when oxidative stress induces extensive cell death and organ failure.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In keeping with previous studies from our 7,8,24 and other laboratories, 25,26 H 2 O 2 concentrations used in this paper are within the submillimolar range, and induce negligible EC death in vitro. Therefore the red/ox imbalance achieved is likely close to what is expected to occur in many pathophysiological conditions, for example, reperfusion injury, when oxidative stress induces extensive cell death and organ failure.…”
Section: Discussionsupporting
confidence: 85%
“…3 miR-200 family has been extensively studied in the epithelial-to-mesenchimal transition (EMT) of cancer cells; 14 in EMT miR-200 family downmodulation enhances cancer aggressiveness and metastases, whereas reintroduction of miR-200 family miRNAs in some tumors inhibits their growth. 14 As ROS inhibit cell proliferation, 7,8,24 we wanted to establish whether some effects of oxidative stress on cell function could be due to miR-200c upregulation.…”
Section: Discussionmentioning
confidence: 99%
“…Cell Cycle Inhibition by Polyamine Depletion-Growth arrest can be manifested as a result of reduced availability of growthstimulating proteins such as cyclin D1, whose level was previously demonstrated to decline rapidly in stressed cells due to attenuated translation and accelerated degradation (40,51,52). We demonstrate here that the level of the cyclin D1 protein declines in DFMO-treated cells (Fig.…”
Section: Comparison Between Expression Patterns Of Growth Arrest and supporting
confidence: 61%
“…15,24,25) and Ca 2ϩ participates in several pathways that induce cell cycle arrest. 15,24) Santini et al found that the calcineurin/nuclear factor of activated T-cell (NFAT) pathway, which is activated by intracellular Ca 2ϩ and induces p21 expression, is involved in cell cycle arrest during keratinocyte differentiation induced by the addition of Ca 2ϩ . 47) Our results together with others findings suggest that an increase in intracellular Ca 2ϩ is involved in p21 expression, resulting in cell cycle arrest in H 2 O 2 -treated H9c2 cells.…”
Section: Discussionmentioning
confidence: 99%